A comparative study on the effects of air gap wind and walking motion on the thermal properties of Arabian Thawbs and Chinese Cheongsams. Issue 8 (2nd August 2016) - Cui, Zhiying; Fan, Jintu; Wu, Yuenshing
Abstract: This paper reports on an experimental investigation on the effects of air gap, wind and walking motion on the thermal properties of traditional Arabian thawbs and Chinese cheongsams. Total thermal resistance ( I t ) and vapour resistance ( R e ) were measured using the sweating fabric manikin – 'Walter', and the air gap volumes of the garments were determined by a 3D body scanner. The results showed the relative changes of It and Re of thawbs due to wind and walking motion are greater than those of cheongsams, which provided an explanation of why thawbs are preferred in extremely hot climate. It is further shown that thermal insulation and vapour resistance of thawbs increase with the air gap volume up to about 71, 000 cm 3 and then decrease gradually. Thawbs with higher air permeability have significantly lower evaporative resistance particularly under windy conditions demonstrating the advantage of air permeable fabrics in body cooling in hot environments. Practitioner Summary: This paper aims to better understand the thermal insulation and vapour resistance of traditional Arabian thawbs and Chinese cheongsams, and the relationship between the thermal properties and their fit and design. The results of this study provide a scientific basis for designing ethnic clothing used in hot environments.